Emotional processes of reading and learning in an illustrated non-fiction book and in a textbook - Sanjuán-Álvarez, Marta; Cristóbal-Hornillos, Rubén (PUBLICACIONES, 2022)
The consideration of the emotional processes of learning is a growing didactic line, as well as the edition of nonfiction illustrated books for children and young readers. The “new nonfiction” shows a hybridisation of genres, textual structures and semantic codes. Its careful format, interactive resources and abundant illustrations add aesthetic and playful components to reading and learning, while still offering rigorous content. These characteristics distinguish them from informative books and, above all, from textbooks. To what extent do they also add important emotional components to the cognitive processes of learning, usually prioritized? Which of its features create and reinforce “opportunities for learning”? Using the criteria of the Orbis Pictus Award Committee, we analysed a nonfiction illustrated book about ancient Egypt and contrasted it with the didactic unit of a 1st ESO book on the same subject. The results show that the organization, design and style of the nonfiction work make information attractive, stimulate the attitude of inquiry, creativity and play, reinforce the construction of meaning through recursive reading and fuse the cognitive and emotional components of reading and learning, far from the mere assimilation of informative content. In conclusion, the nonfiction work turns learning into a vivid experience, as compared to the more expository and cold approach of the textbook.